Syncope with atypical trunk convulsions in a patient with malignant arrhythmia - Doležalová, Irena; Brázdil, Milan; Rektor, Ivan; Tyrlíková, Ivana; Kuba, Robert (Epileptic disorders, 2013)
Syncope is a condition often misdiagnosed as epilepsy. Syncope caused by cardiac disturbance is a life-threatening condition and accurate diagnosis is crucial for patient outcome. We present a case study of a 71-year-old woman who was referred to our epilepsy centre with a diagnosis of refractory epilepsy. We diagnosed convulsive syncope caused by malignant cardiac arrhythmia based on the presence of cardiac asystole lasting for 20-30 seconds, which was caused by sick sinus syndrome combined with third-degree atrioventricular block. The most prominent feature of this syncope was atypical trunk (abdominal or thoracoabdominal) convulsions, which were accompanied by other motor signs (head and eye deviation and brief jerks of the extremities). In the periods between attacks, all investigations, including standard 12-lead ECG and 24-hour ECG monitoring, were normal. This case study highlights the challenge in differential diagnosis of sudden loss of consciousness. [Published with video sequences].
Keywords: diferenciální diagnóza; Epilepsy; Female; Atrioventricular Block; ženské pohlaví; atrioventrikulární blokáda; lidé; synkopa; Sick Sinus Syndrome; Syncope; Electrocardiography; elektrokardiografie; Diagnosis, Differential; epilepsie; syndrom chorého sinu; Aged; senioři; elektroencefalografie; Electroencephalography; Humans